2012
DOI: 10.1002/jib.49
|View full text |Cite
|
Sign up to set email alerts
|

125thAnniversary Review: Bacteria in brewing: The good, the bad and the ugly

Abstract: Beer is a beverage that is produced in a multistage process, where some stages of that process are intentionally influenced by microorganisms, while at other stages of the production process microorganisms are actively discouraged. Most of the intentional microbial activity is facilitated by yeast; however bacteria also play an influential role in beer production. This paper will describe the beneficial role of bacteria in the beer production process (the Good), but will also pay due attention to the negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 133 publications
0
83
0
Order By: Relevance
“…Corresponding to a lower degree of fermentation, pH values for the alcohol-free beers are higher, ranging between 4.61 (KBI 5.4), and The pH value dropped during the first 24 h of fermentation by values ranging from 0.7 for KBI 5.4 to 1.0 for KBI 22.2 with only marginal changes thereafter (data not shown). Due to the high starting pH of the wort of 5.7, the beers, except WLP001, did not reach pH values below 4.5, which are desired in order to serve as one of the microbial hurdles for beer spoiling bacteria to overcome [37]. However, lower pH values can be reached with a lower starting pH of the wort, which can be adjusted; i.e., by lactic acid, the use of sour malt or biological acidification.…”
Section: Fermentation Performancementioning
confidence: 99%
“…Corresponding to a lower degree of fermentation, pH values for the alcohol-free beers are higher, ranging between 4.61 (KBI 5.4), and The pH value dropped during the first 24 h of fermentation by values ranging from 0.7 for KBI 5.4 to 1.0 for KBI 22.2 with only marginal changes thereafter (data not shown). Due to the high starting pH of the wort of 5.7, the beers, except WLP001, did not reach pH values below 4.5, which are desired in order to serve as one of the microbial hurdles for beer spoiling bacteria to overcome [37]. However, lower pH values can be reached with a lower starting pH of the wort, which can be adjusted; i.e., by lactic acid, the use of sour malt or biological acidification.…”
Section: Fermentation Performancementioning
confidence: 99%
“…In general, food alteration derives from contamination mediated by specific microorganisms, but sometimes several pathogens can simultaneously contaminate a food matrix (Fusco & Quero, 2014). For example, brewing could be negatively affected by different classes of bacteria such as lactic acid bacteria, acetic acid bacteria, Enterobacteriaceae, Zymomonas (Vriesekoop et al, 2012) that can coexist. In these cases, HTS analysis is reliable to identify any undesirable microorganism and could be used to enhance food sanitation and preservation measures.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Data suggested that beer is characterized by consistent modification in microbial activity at every stage, from raw material production and malting to stability in the package. Again, HTS approach allowed to evaluate this diversity and to exclude the presence of undesirable bacteria (Vriesekoop, Krahl, Hucker, & Menz, 2012).…”
Section: Microbiota Composition and Dynamics In Plant Fermentation Prmentioning
confidence: 99%
“…Excellent reviews on beer spoilage bacteria have been published in recent years by Suzuki (2011), Vriesekoop et al (2012 and Bokulich and Bamforth (2013). The Journal of the Institute of Brewing's archive (1890-present) also provides an excellent source of information on brewing microbiology aspects.…”
Section: Further Readingmentioning
confidence: 99%